Utilization of Biotechnology for Coral Reef Engineering and Conservation in the Face of Climate Change - Aisyah Mutia Dawis; Alna Alviche (CV. Get Press Indonesia, 2024)
This research aims to develop and test biotechnological methods that can increase coral reef resilience to environmental stress due to climate change. Symbiodinium spp. were genetically engineered, probiotics were administered, and tissue culture was conducted. The results showed that engineered corals showed higher temperature tolerance, lower bleaching rates, faster growth, and increased survival in both the laboratory and field. These results suggest that the application of biotechnology, including genetic engineering, tissue culture, and coral probiotic applications, is effective in increasing coral resilience and health in the face of climate change impacts to coral reef ecosystems. This method provides an innovative and applicable solution for coral reef conservation and restoration. This research is expected to provide concrete solutions to support the sustainability of marine ecosystems in the future.